Pan-Cancer Analysis of the Solute Carrier Family 39 Genes in Relation to Oncogenic, Immune Infiltrating, and Therapeutic Targets - Qu, Yi-Yuan; Guo, Rong-Yan; Luo, Meng-Ling; Zhou, Quan (Frontiers in Genetics, 2021)
Background: Emerging pieces of evidence demonstrated that the solute carrier family 39 (SLC39A) members are critical for the oncogenic and immune infiltrating targets in multiple types of tumors. However, the precise relationship between the SLC39A family genes and clinical prognosis as well as the pan-cancer tumor cell infiltration has not been fully elucidated. Methods: In this study, the pan-cancer expression profile, genetic mutation, prognostic effect, functional enrichment, immune infiltrating, and potential therapeutic targets of the SLC39A family members were investigated by analyzing multiple public databases such as the Oncomine, TIMER, GEPIA, cBioPortal, KM-plotter, PrognoScan, GeneMANIA, STRING, DAVID, TIMER 2.0, and CellMiner databases. Results: The expression levels of most SLC39 family genes in the tumor tissues were found to be significantly upregulated compared to the normal group. In mutation analysis, the mutation frequencies of SLC39A4 and SLC39A1 were found to be higher among all the members (6 and 4%, respectively). Moreover, the overall mutation frequency of the SLC39A family genes ranged from 0.8 to 6% pan-cancer. Also, the function of the SLC39A highly related genes was found to be enriched in functions such as zinc II ion transport across the membrane, steroid hormone biosynthesis, and chemical carcinogenesis. In immune infiltration analysis, the expression level of the SLC39A family genes was found to be notably related to the immune infiltration levels of six types of immune cells in specific types of tumors. In addition, the SLC39A family genes were significantly related to the sensitivity or resistance of 63 antitumor drugs in a variety of tumor cell lines. Conclusion: These results indicate that the SLC39 family genes are significant for determining cancer progression, immune infiltration, and drug sensitivity in multiple cancers. This study, therefore, provides novel insights into the pan-cancer potential targets of the SLC39 family genes.